The effectivity of ozone water application on tampon in post posterior tooth extraction in Department of Oral Surgery and Maxillofacial Faculty of Dentistry, University of North Sumatera (USU) - Hendry Rusdy; Abdullah Oes; Indra B. Siregar; David Sitompul (DiscoverSys Inc., 2018)
Objective: Tooth extraction in oral surgery can lead to bleeding. Ozone water is a material that is able to accelerate healing process and prevent socket inflammation by stimulating and speeding up the work of cells like fibroblasts. Moreover, ozone water quickens the release of oxygen to the tissue to kill microorganism in tooth socket and accelerate healing process.Material and Methods: This is experimental research using post-test only with control group design. Ozone water is made using DSM Aero High Voltage. The ozonation process takes 30 minutes and followed by soaking a tampon in the ozone water. Patients in the treatment group bite the tampon for 30 minutes while patients in the control group bite a dry tampon. After 30 minutes, the tooth socket is checked to observe the inflammation using the Gingival Score Index. Patients are instructed to come back 7 days after the tooth extraction to check on the inflammation. There is a total of 38 samples in the study and they are divided into 2 groups (treatment and control). This study is conducted in the Department of Oral Surgery and Maxillofacial Faculty of Dentistry USU.Results: The average of Gingival Index after 30 minutes is 0.42±0.507 and 0.95±0.911 for treatment and control groups, respectively. On day 7 the average is 0.00±0.00 for treatment group and 0.37±0.496 for control group.Conclusion: Ozone water is able to stimulate and quicken the healing process for wounds and reduce the inflammation of the tooth socket.